INFLUENCE OF THE COBALT NITRATE:ETHYLENE GLYCOL MOLAR RATIO ON THE FORMATION OF CARBOXYLATE PRECURSORS AND COBALT OXIDES - DIPPONG, Thomas; GOGA, Firuța; AVRAM, Alexandra (Studia Universitatis Babeș-Bolyai Chemia, 2017)
This paper focuses on the obtaining of carboxylate precursors through the redox reaction of cobalt nitrate and ethylene glycol, in different stoechiometric ratios, as well as the decomposition of precursors into cobalt oxides. The influence of the NO3−:C2H6O2 stoichiometric ratio on the formation of the precursors is studied through thermal analysis, FTIR spectroscopy and acido-basic analysis (conductometric/potentiometric titrimetry). Phase analysis by XRD and FTIR of the powders obtained at the decomposition of the precursors at 400°C has evidenced the formation of CoO for a high NO3-:C2H6O2 synthesis ratio and of Co3O4 for a low NO3−:C2H6O2 ratio. The Scherrer equation and scanning electron microscopy (SEM) were used to determine the dimensions of the nanoparticles obtained.